Molecular evolution and depth-related adaptations of rhodopsin in the adaptive radiation of cichlid fishes in Lake Tanganyika - Ricci, Virginie; Ronco, Fabrizia; Musilova, Zuzana; Salzburger, Walter (Molecular ecology, 2022)
The visual sensory system is essential for animals to perceive their environment and is thus under strong selection. In aquatic environments, light intensity and spectrum differ primarily along a depth gradient. Rhodopsin (RH1) is the only opsin responsible for dim-light vision in vertebrates and has been shown to evolve in response to the respective light conditions, including along a water depth gradient in fishes. In this study, we examined the diversity and sequence evolution of RH1 in virtually the entire adaptive radiation of cichlid fishes in Lake Tanganyika, focusing on adaptations to the environmental light with respect to depth. We show that Tanganyikan cichlid genomes contain a single copy of RH1. The 76 variable amino acid sites detected in RH1 across the radiation were not uniformly distributed along the protein sequence, and 31 of these variable sites show signals of positive selection. Moreover, the amino acid substitutions at 15 positively selected sites appeared to be depth-related, including three key tuning sites that directly mediate shifts in the peak spectral sensitivity, one site involved in protein stability and 11 sites that may be functionally important on the basis of their physicochemical properties. Among the strongest candidate sites for deep-water adaptations are two known key tuning sites (positions 292 and 299) and three newly identified variable sites (37, 104 and 290). Our study, which is the first comprehensive analysis of RH1 evolution in a massive adaptive radiation of cichlid fishes, provides novel insights into the evolution of RH1 in a freshwater environment.
Keywords: molekulární evoluce; Cichlids; spectral tuning; Phylogeny; ryby; freshwater fish; cichlidy; opsin; Evolution, Molecular; vision; Lakes; zvířata; Tanzanie; jezera; rodopsin; Fishes; photic environment; fylogeneze; voda; Tanzania; rod photoreceptor; Water; Animals; Rhodopsin